2005
DOI: 10.3732/ajb.92.11.1836
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive developmental complexity in the African oil palm (Elaeis guineensis, Arecaceae)

Abstract: Species of the palm family (Arecaceae) are remarkably diverse in their inflorescence and floral morphologies, which make them a particularly interesting group for studies of reproductive development and its evolution. Using light and scanning electron microscopy, we describe inflorescence and flower development in the African oil palm Elaeis guineensis from the initiation of the inflorescence meristem to flower maturity. In mature palms, the inflorescence develops over 2-3 years and is characterized by individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 30 publications
1
82
0
9
Order By: Relevance
“…For an example; in oil palm (Elaeis guineensis Jacq), 5% of somatic embryo-derived palms showed an abnormality that is called the 'mantled' phenotype [26]. This is claimed to be a somaclonal variation resulting in a conversion of the male floral organs into supernumerary carpels [27] and may lead to partial or complete flower sterility, depending on the severity of the abnormality [26]. It has been reported that hypo-methylation during tissue culture contributes to the origin of this 'mantled' phenotype in tissue culture effectively preventing the clonal propagation from elite palms [28].…”
Section: Resultsmentioning
confidence: 99%
“…For an example; in oil palm (Elaeis guineensis Jacq), 5% of somatic embryo-derived palms showed an abnormality that is called the 'mantled' phenotype [26]. This is claimed to be a somaclonal variation resulting in a conversion of the male floral organs into supernumerary carpels [27] and may lead to partial or complete flower sterility, depending on the severity of the abnormality [26]. It has been reported that hypo-methylation during tissue culture contributes to the origin of this 'mantled' phenotype in tissue culture effectively preventing the clonal propagation from elite palms [28].…”
Section: Resultsmentioning
confidence: 99%
“…Developmental data on the arecoid floral triad have been recently published for commercially important species such as Cocos (Perera et al, 2010) and Elaeis (Adam et al, 2005), but almost nothing is known about inflorescence development in other arecoid palms. Moreover, apart from the study describing selected developmental stages of acervuli in Hyophorbe indica (Uhl and Moore, 1978), relatively few data have been obtained on the ontogeny of this type of partial inflorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Diferensiasi sexual, tahapan yang menentukan apakah bunga kelapa sawit akan menjadi bunga jantan atau betina akan terjadi "sesaat" sebelum bunga berkembang tumbuh (Leaf+15). Menurut Adam et al (2005) pada tanaman kelapa sawit Afrika (Elaeis Guineensis, Arecaceae), differensiasi ini terjadi pada level Leaf+12. Menurut pengalaman Dr. Asmini Budiani (komunikasi pribadi), secara histokimia seluler tanda diferensiasi seksual pada kelapa sawit hibrida Tenera mulai terlihat pada level Leaf+11.…”
unclassified